Economic Analysis of Increasing Foot-and-Mouth Disease Vaccination Frequency: The Case of the Biannual Mass Vaccination Strategy - Ozturk, Nursen; Kocak, Omur; Vosough Ahmadi, Bouda (Frontiers in Veterinary Science, 2020)
Biannual mass vaccination is a routinely applied Foot and Mouth Disease (FMD) control strategy in Turkey. However, due to the fact that biannual mass vaccination may leave significant immunity gaps this strategy may cause economic losses because of the possible FMD infections. In high risk areas-such as border cities, it was suggested to increase the vaccination intervals in order to decrease the FMD infection risk. This study discuss and compare the economic effects of biannual mass vaccination and vaccination in each four months strategies in border cities by using partial budgeting approach. Biannual mass vaccination was served as a baseline scenario. Data on the impact of FMD on animal health and production parameters for 2018 were obtained from the OIE-WAHIS system and complemented by literature and expert views. In partial budgeting approach, weight loss was considered as the major loss of income due to majority of animal husbandry is based on cattle fattening in border cities of Turkey. The result of the study revealed that net economic impact which is the benefit that exceeds the lost and costs of increasing the frequency of vaccination, is 36.1 TL (7.5) per cattle. The sensitivity analysis showed that average body weight and weight loss when infection had more effect on net impact than market prices. The lower and upper FMD incidence changes resulted in 11.9 TL (2.5) and 71.1 TL (14.8) of net impact per cattle, respectively. The new FMD control strategy would make a net economic impact of 5,368,634.3 TL (1,113,824.4) as total for population of 800,970 animal in border cities. The results of this study indicated that intense FMD control strategies may be more cost-effective than the current control strategy especially in high risk areas. Future studies with improved data quality must be conducted which focus on to identify the most cost-effective FMD control strategies on nationwide.